Double-decker lutetium phthalocyanine functionalized with 4-phenylthia-zol-2-thiol moieties: Synthesis, characterization, electrochemistry, spectroelectrochemistry and electrochromism - KOCA, ATIF; BUDAK, ÖZLEM (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, the synthesis, spectral characterization, electrochemistry, spectroelectrochemistry and electro-chromism of a novel double-decker lutetium phthalocyanine, bis-[2(3),9(10),16(17),23(24)-tetrakis-[2-(4-phenyl-2-thiazolyl)sulfanyl] phthalocyaninatolutetium(III), denoted as LuPc2, is reported. The LuPc2 synthe-sized in this study is unique, being the first thiazole-containing double-decker lutetium phthalocyanine complex published to date. The electrochemistry of LuPc2 was used to support the proposed sandwich structure. A characteristic first reduction couple at 0.32 V indicated reduction of the radical Pc ring of LuPc2. The other redox process indicated electron transfer reactions of each Pc ring, which is in harmony with other sandwich type Pc complexes. Distinct color changes of LuPc2 in solution showed its possible use in the solid state as an electro-chromic material; thus, the electrochromic responses were analyzed using a LuPc2 film. Fast, stable and reversible electrochromic responses were observed with green to red color changes.
Keywords: Phthalocyanines; Thiazole; Lutetium; Electrochemistry; Spectroelectrochemistry; OPTICAL LIMITING PROPERTIES; THIN-FILMS; COMPLEXES; BIS; BEHAVIOR